2014
DOI: 10.4103/0970-9290.131126
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical study comparing metallic and glass fiber post in restoration of endodontically treated teeth

Abstract: Glass FRPs performed better than the metallic post based on short-term clinical performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 2 publications
3
25
0
5
Order By: Relevance
“…Most studies that evaluated metal and fiber posts 21,22,23,27 found similar survival rates for both types of retainers, except for Schmitter et al 4 that found higher survival for glass fiber posts and King et al, 24 that found higher survival for metal posts. Interestingly, these studies show a longer follow-up period than Gbadebo et al, 21 Sarkis-Onofre et al, 22 Sterzenbach et al, 23 and Cloet et al 27 It is probable that a longer evaluation period would be needed to detect possible differences in the latter studies.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Most studies that evaluated metal and fiber posts 21,22,23,27 found similar survival rates for both types of retainers, except for Schmitter et al 4 that found higher survival for glass fiber posts and King et al, 24 that found higher survival for metal posts. Interestingly, these studies show a longer follow-up period than Gbadebo et al, 21 Sarkis-Onofre et al, 22 Sterzenbach et al, 23 and Cloet et al 27 It is probable that a longer evaluation period would be needed to detect possible differences in the latter studies.…”
Section: Discussionmentioning
confidence: 95%
“…Five st ud ie s compa red f ib er a nd me t a l posts, 4,21,22,23,24 two studies compared metal posts, 25,26 one study compared prefabricated fiber, custommade fiber and metal posts, 27 one study compared prefabricated and custom-made fiber posts, 28 one study compared three types of fiber posts 29 and one study compared two types of fiber posts. 30 Mean time of follow-up varied from 19.2 months to 109 months.…”
Section: 13mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous clinical and in vitro studies showed that the incidence of post debonding, could be reduced with good post fitting, which is a key factor for the clinical success of restorations 13,14 . Therefore, the routine use of anatomic fiber posts was recommended when the prepared root canal is too wide or not perfectly round.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive preparation of the root canal may reduce the strength of the root dentin walls, which significantly decreases their fracture resistance [7]. When the coronal tooth structure has been reduced to less than half, posts are needed to restore the strength [8].…”
Section: Introductionmentioning
confidence: 99%